2020
DOI: 10.1101/2020.05.04.077628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antagonistic control of DDK binding to licensed replication origins by Mcm2 and Rad53

Abstract: Eukaryotic replication origins are licensed by the loading of the replicative DNA helicase, Mcm2-7, in inactive double hexameric form around DNA. Subsequent origin activation is under control of multiple protein kinases that either promote or inhibit origin activation, which is important for genome maintenance. Using the reconstituted budding yeast DNA replication system, we find that the flexible N-terminal tail of Mcm2 promotes the stable recruitment of Dbf4-dependent kinase (DDK) to Mcm2-7 double hexamers, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…Figure 1B shows that DDK pre-phosphorylated with Rad53 was unable to promote replication (lane 3), while preincubation of DDK with ATP alone (lane 2) or with ATP and the kinase-dead Rad53 mutant (lane 4) had no effect on replication. Whilst this work was in progress, Wahab and Remus showed that, in their system, binding of Rad53 to Dbf4 is sufficient to inhibit its ability to interact with the MCM double hexamer (Abd Wahab and Remus, 2020). In our hands, the kinase dead Rad53 did not inhibit replication.…”
Section: Rad53 Inhibition Of Origin Firing In Vitro Via Dbf4 and Sld3mentioning
confidence: 68%
“…Figure 1B shows that DDK pre-phosphorylated with Rad53 was unable to promote replication (lane 3), while preincubation of DDK with ATP alone (lane 2) or with ATP and the kinase-dead Rad53 mutant (lane 4) had no effect on replication. Whilst this work was in progress, Wahab and Remus showed that, in their system, binding of Rad53 to Dbf4 is sufficient to inhibit its ability to interact with the MCM double hexamer (Abd Wahab and Remus, 2020). In our hands, the kinase dead Rad53 did not inhibit replication.…”
Section: Rad53 Inhibition Of Origin Firing In Vitro Via Dbf4 and Sld3mentioning
confidence: 68%
“…Figure 1B shows that DDK pre-phosphorylated with Rad53 was unable to promote replication (lane 3), while pre-incubation of DDK with ATP alone (lane 2) or with ATP and the kinase-dead Rad53 mutant (lane 4) had no effect on replication. Whilst this work was in progress, Abd Wahab and Remus also found that Rad53 could directly inhibit DDK action at origins (Abd Wahab and Remus, 2020).…”
Section: Rad53 Inhibition Of Origin Firing In Vitro Via Dbf4 and Sld3mentioning
confidence: 95%
“…It has been suggested that Rad53 can inhibit one of its targets, DDK, by direct binding as well as by phosphorylation (Abd Wahab and Remus, 2020). We therefore asked whether we could detect stable interactions between Mrc1 and Rad53 by coimmunoprecipitation using the same buffer conditions used in the in vitro replication assay.…”
Section: Rad53 Inhibition Of Replication Elongation Via Mrc1 and Mcm10mentioning
confidence: 99%
“…In budding yeast however, the checkpoint kinase Rad53 blocks late origin firing, not by inhibition of CDK activity, but by directly inhibiting two replication initiation factors; the DDK subunit Dbf4 and the CDK target Sld3 (Lopez-Mosqueda et al, 2010;Zegerman and Diffley, 2010). Rad53-dependent phosphorylation of Sld3 inhibits its interactions with various other replication factors including Dpb11 (Lopez-Mosqueda et al, 2010;Zegerman and Diffley, 2010), while recent work has shown that direct interaction between Rad53 and Cdc7-Dbf4 prevents DDK from binding to the Mcm2-7 complex (Abd Wahab and Remus, 2020). In higher eukaryotes, in addition to inhibition of CDK activity, the checkpoint can also inhibit origin firing through direct targeting of the Sld3 orthologue Treslin (Boos et al, 2011;Guo et al, 2015) and DDK (Costanzo et al, 2003;Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%